Minjiwarra: archaeological evidence of human occupation of Australia's northern Kimberley by 50, 000 BP. Issue 2 (4th May 2019) - Veth, Peter; Ditchfield, Kane; Bateman, Mark; Ouzman, Sven; Benoit, Marine; Motta, Ana Paula; Lewis, Darrell; Harper, Sam
Abstract: Recent archaeological research in Australia's north-eastern Kimberley has luminescence dated a large red sedimentary feature, known as Minjiwarra, with artefacts in stratified contexts from the late Holocene to ∼50, 000 years ago. This site is located on the Drysdale River, with preliminary excavations undertaken as part of an ARC Linkage Project. Deeply stratified sites in association with rockshelters are uncommon across the NE Kimberley and basal dates at open cultural deposits vary greatly. Most of them are mid-Holocene in age. However, Minjiwarra appears to cover the entire span of potential human occupation in this region, with associated lithic technology, reported on here.